Tracheal resection in patients post–COVID-19 is associated with high reintervention rate and early restenosisCentral MessagePerspective - Filippos-Paschalis Rorris, MD; Evangelia Chatzimichali, MD; Evangelia Liverakou, MD; Constantine N. Antonopoulos, MD, PhD; Evangelos Balis, MD; Constantinos Kotsifas, MD; Grigoris Stratakos, MD, PhD; Antonia Koutsoukou, MD, PhD; Charalampos Zisis, MD, PhD (JTCVS Techniques)
Objectives: A remarkable increase in the number of patients presenting with tracheal complications after prolonged endotracheal intubation and mechanical ventilation for the management of the severe COVID-19–associated respiratory failure has been observed. In this study, we assessed the postoperative outcomes of tracheal resection in patients with COVID-19. Methods: We conducted a retrospective study in which all patients with a history of prolonged invasive mechanical ventilation due to COVID-19 infection, who were treated with tracheal resection and reconstruction, were included. The primary objective was in-hospital mortality and postoperative reintervention rate. The secondary objective was the time to tracheal restenosis. Results: During the 16-month study period, 11 patients with COVID-19 with tracheal complications underwent tracheal resection with end-to-end anastomosis. Mean patient age was 51.5 ± 9 years, and the majority were male (9 patients). Eight patients were referred for management of postintubation tracheal stenosis, and 3 patients were referred for tracheoesophageal fistula. Eight patients had a history of tracheostomy during the COVID-19 infection hospitalization. There was 1 in-hospital death (9.1%) due to septicemia in the intensive care unit approximately 2 months after the operation. Postoperatively, 32 reinterventions were required for tracheal restenosis due to granulation tissue formation. The risk for reintervention was higher during the first 3 months after the index operation. Four patients developed tracheal restenosis (36.4%), and 2 of them required endotracheal stent placement during the follow-up period. Conclusions: Tracheal resection and reconstruction after COVID-19 infection are associated with a high reintervention rate postoperatively. Such patients require close follow-up in expert interventional pulmonology units, and physicians should be on high alert for the early diagnosis and optimal management of tracheal restenosis. Video Abstract: